Pengaruh Naungan dan Pupuk Kandang Terhadap Iklim Mikro dan Pertumbuhan Tanaman Cabai Di Tanah Pasiran - Rex Konstantinus Lingitubun; Yosefina Mangera; Wahida Wahida (Musamus AE Featuring Journal, 2019)
The purpose of this study was to determine the effect of providing shade and manure variations on the microclimate and to determine the effect of providing shade and manure variations on the growth of chilli plants in sandy soils. The method used is descriptive analysis for micro climate parameters and randomized block design (RBD). Twelve treatments tested included: TNA (without shade + chicken manure). TNS (without shade + cow manure). TNK (without shade + goat manure). TNT (without shade + without manure). NHA (shade black + chicken manure). NHS (black shade + cow manure). NHK (black shade + goat manure. NHT (black shade + without manure). NBA (blue shade + chicken manure). NBS (blue shade + cow manure). NBK (blue shade + goat manure). NBT (blue shade + without manure).The research results show that the use of black shade with cow manure has the highest average soil moisture content during the study ie 6.58% while the lowest average moisture content during the study was owned by the treatment without shade and without manure with soil moisture value 1.39%. the shade treatment was able to provide a lower temperature. the blue shade provided an average temperature of 33.21°C . black shade 34.98°C. while without shade 35.87°C. The highest humidity was shown in the treatment of blue shade 68%. black shade 65%. while without shade 63%. Shade treatment with manure is able to reduce soil temperature. indicated by the highest soil temperature in the treatment without shade + without manure 36.41°C and the lowest temperature in the treatment of blue shade + chicken manure 33.89°C. The shade treatment is able to reduce wind speed compared to the treatment without shade. indicated by the lowest value in the treatment of blue shade 11.20 m/s. black shade 11.29 m/s. while the highest value is in the treatment without shade 11.48 m/s . Analysis of variance of shade treatment with manure for plant growth parameters were not significantly different. this could be due to genetic factors of the plant. as well as production components based on analysis of variance for all treatments not significantly different. These results are more influenced by extreme climatic factors at the time of conception so that there is an attack of fruit rot disease which results in suboptimal yields.